The goblin spider genus Xyphinus (Araneae; Oonopidae) - Kranz-Baltensperger, Yvonne (Zootaxa, 2014)
The goblin spider genus Xyphinus Simon 1893 presents several peculiar characters, such as spines and spikes on carapace and abdomen in different sizes and shapes, strongly modified male palps with distinct apophyses and female epigastric modifications with sclerotized scapi, which can be short or long or even contorted. The genus is restricted to the Old World tropics, except for one species collected also in Australia; as revised here, the group currently comprises 20 species, 10 are newly described: X. holgeri sp. nov., X. deelemanae sp. nov., X. acutus sp. nov., X. sabal sp. nov., X. krabi sp. nov., X. infaustus sp. nov., X. rogerfedereri sp. nov., X. pachara sp. nov., X. baehrae sp. nov., and X. distortus sp. nov. Pseudotriaeris Brignoli 1974 is placed as junior synonym of Xyphinus.